IMPACT OF DIGITAL TRANSFORMATION ON ACCOUNTING AND AUDIT IN UZBEKISTAN: EFFICIENCY AND CHALLENGES - Avilov Nematjon , Yuldashevich (THE INNOVATION ECONOMY, 2025)
This article examines the impact of digital transformation on accounting and auditing in Uzbekistan, focusing on financial reporting quality, process efficiency, and compliance with international standards (IFRS, ISA). The study explores the adoption of technologies such as ERP systems, artificial intelligence, and blockchain. A mixed methods approach was employed, combining qualitative analysis (of legislation and enterprise documents) and quantitative analysis (of statistical data for 2020–2024). Findings indicate that digitalization has reduced error rates and enhanced transparency, but challenges such as insufficient staff qualifications, infrastructure limitations, and financial constraints persist. Practical recommendations tailored to Uzbekistan’s context are provided.